Merritt's neurology - Louis, Elan D.; Mayer, Stephan A. (Philadelphia : Wolters Kluwer, 2022)
This edition of Merritt's is fully updated and includes comprehensive revisions reflecting remarkable progress made in recent years in neurology research, including new and emerging treatments for diseases previously without effective pharmacotherapy. New material includes updates on imaging and interventional therapy for stroke, the latest approved agents for migraine, epilepsy, and multiple sclerosis and new material on neurologic care in the developing world, neuro-coronavirus disease, septic encephalopathy, and addiction medicine--
Includes bibliographical references and index.
Keywords: Nervous System Diseases